Two-Year Follow-Up of Clinical Efficacy of Femtosecond Laser, Modified Capsular Tension Ring, and Iris Hook-Assisted Surgical Treatment of Lens Subluxation in Patients with Elevated Intraocular Pressure - Chao Wang; Yuhua Rui; Yi Zhou; Tu Hu; Xiaobo Xia; Jian Jiang (Journal of Ophthalmology)
Purpose. To evaluate the outcomes of femtosecond laser, modified capsular tension ring, and iris hook-assisted surgical treatment of lens subluxation in patients with elevated intraocular pressure (IOP). Methods. Fifteen patients with lens subluxation and elevated IOP were enrolled in this study. All patients underwent femtosecond-laser-assisted cataract surgery/phacoemulsification/intraocular lens implantation/modified capsular tension ring (MCTR) implantation with iris hook assistance. Uncorrected visual acuity (UCVA), best corrected visual acuity (BCVA), IOP, number of glaucoma medication complications, endothelial cell density (ECD), and tilt of the lens were recorded before and after surgery. All patients were observed for 24 months postoperatively. Results. UCVA and BCVA increased significantly at 1 month, 6 months, 12 months, and 24 months, compared with preoperative UCVA and BCVA (P<0.001). IOP significantly decreased at 1 month, 3 months, 6 months, 12 months, and 24 months, compared with preoperative IOP (P<0.001). 3 patients received glaucoma medications to control IOP after surgery. All medications were discontinued at 3 months postoperatively. Conjunctival redness or hemorrhage was observed in 11 patients (73.3%); transient corneal edema was observed in 3 patients (20.0%); and posterior capsule opacification occurred in 1 patient (6.67%). The ECD and tilt of the lens are within an acceptable range. Conclusion. The combined use of a femtosecond laser, MCTR, and iris hooks is an effective and safe method for treating patients with lens subluxation and elevated IOP.